Π-Conjugation effect on the aggregation-induced emission of extended viologens. (10th December 2020) - Tonga, Murat
Abstract : The aggregation-induced emission properties of extended viologens, particularly the effect of π-conjugation, were methodically studied. Abstract : This work focuses on the AIE properties of extended viologens (EVs), specifically the effect of π-conjugation by employing several aryl groups including phenyl, naphthyl, and anthryl. The DFT calculations show that these EVs with larger aryl groups adopt a twisted geometry due to steric hindrance between the aryl and vinylene–pyridinium units, while the EV with a phenyl ring adopted a planar one.